Battery cell with high rate capability, battery, preparation method and device

By coating polymer material on the battery separator and heating and applying ultrasonic waves in a high-temperature fixture, the polymer material is cross-linked with the battery material and sheared, the problem of deformation and uneven dispersion of conductive agents during high-speed charging and discharge is solved, and the battery magnification characteristics and service life are improved.

CN119812675AActive Publication Date: 2025-04-11AMPREUS WUXI CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411948645.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-11
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

Existing batteries are prone to deformation during high-rate charging and discharging, resulting in a decrease in battery energy density and shortening of service life, and uneven dispersion of conductive agents affects the dynamic performance of the battery.

Method used

By applying a polymer material coating on the separator of the battery, heating and applying ultrasonic waves in a high-temperature fixture, the polymer material reacts with the positive electrode and the negative electrode materials, and the crosslinking effect is controlled through ultrasonic shearing treatment to ensure uniform dispersion of the conductive agent.

Benefits of technology

While ensuring the low battery hardness and cyclic expansion rate, the battery's magnification characteristics and charging and discharge performance are significantly improved, and the battery's service life is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812675A_ABST
    Figure CN119812675A_ABST
Patent Text Reader

Abstract

The invention discloses a battery cell with high rate performance, a battery, a preparation method and a preparation device. The preparation method comprises the following steps: coating a high polymer material coating on a diaphragm of the battery; assembling the diaphragm containing the high polymer material coating, the positive plate containing the positive electrode material and the negative plate containing the negative electrode material into a semi-finished battery cell, injecting electrolyte, placing the semi-finished battery cell between two clamping plates, and applying pressure, so that the positive plate, the negative plate and the diaphragm are tightly attached together; the two clamping plates are used for carrying out heating crosslinking and ultrasonic shearing on a whole formed by clinging the positive plate, the negative plate and the diaphragm during first charging formation. According to the scheme, during high-temperature formation, the conductive agent is uniformly attached to material particles and uniformly dispersed among particle chains in a state after ultrasonic vibration, shearing and compression effects, so that the situation that the local conductive agent is too strong or too weak is greatly reduced, the diaphragm resistivity of a pole piece is effectively reduced, and the rate characteristic of a battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a battery cell, a battery, a preparation method and a device with high rate performance. Background Art

[0002] With the popularization of electronic products around people, the demand for battery life has been stimulated, and the improvement of battery energy density is imminent. The mainstream electric battery energy density improvement mainly relies on the advancement of material technology, such as the gradual improvement of high-voltage technology for the positive electrode and multi-lithium storage technology for the negative electrode, such as silicon-carbon negative electrode materials. At the same time, other auxiliary materials of the battery are further thinned to improve the battery energy density. While improving the energy density, fast charging and fast discharging technologies have also been developed and applied to various electronic products. The size of electronic products is getting smaller and smaller, and the batteries are getting thinner and thinner. At the same time, for high-rate performance, fast charging and fast discharging must be supported to meet the product usage requirements.

[0003] The thinner the battery thickness is, when using aluminum-plastic film as the shell, in the conventional winding process, due to the winding structure, the direction of the electrode material expansion stress is uneven, which can easily cause the battery to deform during subsequent charging and discharging. After a certain number of cycles, the deformation becomes more and more obvious after the electrical expansion coefficient increases. The deformation will cause the spacing between layers to increase and the migration path of ions to become longer. The battery impedance increases significantly, which will eventually manifest as the battery capacity decaying too fast. In severe cases, the packaging shell of electronic products will be lifted, causing defects. The conventional method in the industry is to apply PVDF or PMMA-type colloids on the diaphragm. After the battery is injected with electrolyte, the electrolyte has a swelling effect on the tape. By placing it in a high-temperature clamping fixture, after clamping, the high temperature will accelerate the swelling of the colloid. The swollen colloid will cross-link with the PVDF in the positive electrode and the binder in the negative electrode, so that the positive electrode, diaphragm, and negative electrode form a trinity. When charging and discharging, the whole formed by its cross-linking can overcome most of the stress of the negative electrode expansion, and the battery is not easy to deform in subsequent cyclic use.

[0004] The demand for high-rate performance, high-rate lithium-ion battery is a lithium-ion battery that can charge and discharge quickly in a short time, can maintain good performance at high rates, and can withstand more charge and discharge cycles, reduce the battery attenuation rate, and thus extend the battery life. It has a wide range of applications in many fields, electric vehicles, drones, energy storage systems, consumer electronics, power tools, cleaning tools, toys, etc. The high-rate characteristic battery, due to its relatively large current density, will release the stress of material expansion faster during the charge and discharge cycle. If no measures are taken to limit it, the force of the positive and negative electrode expansion will also lead to serious deformation of the electrode group. The usual method is to make the battery hard, and also to coat the diaphragm with PVDF or PMMA-type polymer colloids, which swell in the electrolyte at high temperature and cross-link with the colloids in the positive and negative electrodes. The actual trinity overcomes the expansion stress of the positive and negative electrodes during charge and discharge, so that the expansion and deformation of the battery cell can be effectively controlled.

[0005] At the same time, in the demand for high-rate performance batteries, the dispersion of tiny conductive agents in the positive and negative electrodes is also a major factor to be considered. The uniformity of the dispersion of conductive agents in the electrodes is crucial to the performance of the battery. Uneven dispersion of conductive agents may cause a series of problems. Uneven dispersion of conductive agents will lead to uneven current distribution inside the electrode, which will in turn affect the SoC (state of charge) of different parts of the electrode and accelerate the decay rate of the battery. Uneven dispersion of conductive agents will deteriorate the dynamic performance of the battery, such as reducing the rate performance and long-term cycle performance of the battery. Conductive agent agglomeration will cause the electrode resistance at the position without conductive agent to increase significantly, thereby affecting the overall performance of the battery. Generally, the main reasons for the uneven dispersion of conductive agents are that the smaller the carbon black particle size, the higher the carbon black oil absorption value, the lower the carbon black structure, the larger the specific surface area of ​​carbon black, the greater the viscosity in the product, and the worse the dispersion performance. The dispersion process also has a profound impact on uniformity. Improper use of grinding equipment or high-speed stirring and dispersing equipment, inappropriate ratio of dispersant or auxiliary oil, feeding process sequence, and homogenization parameters will all affect the uniformity of dispersion. The usual improvement method is to optimize the dispersion process, select appropriate dispersion equipment and process parameters, such as stirring speed and dispersion time. Use appropriate dispersants and additive oils to improve the dispersion performance of the conductive agent. Adjust the particle size, structure, oil absorption value and other properties of carbon black to improve its dispersion performance. Strengthen the monitoring of parameters such as slurry viscosity, solid content, coating quality, etc. during the production process, and use a film resistor to measure resistivity control.

[0006] Based on the actual practical situation of the above two points, when PVDF or PMMA is swollen by the electrolyte, it cross-links with the polymer substances in the positive and negative electrodes, and the positive electrode, negative electrode, and diaphragm form a trinity effect. This makes the battery harder and less likely to deform. But at the same time, the negative effect is that after PVDF swells, the cross-linking area with the positive or negative electrode is very large, which can easily cause serious blockage of the channels of some diaphragms, affecting the migration of lithium ions and causing the battery's rate characteristics to decrease. The same is true for PMMA. After absorbing the electrolytic swelling, the PMMA glue particles will swell. When the swollen particles form a whole chain area, it will affect the migration of lithium ions. The influence of the pole sheet resistivity on the battery rate characteristics is also profound. Conventional optimization methods are mainly to make improvements in the electrode slurry and coating processes. Therefore, in this context, it is inevitable that the diaphragm needs to be coated with colloid in order to prevent the battery from being easily deformed. When the colloid swells, it is easy to cause the pores of the diaphragm to be blocked, which hinders the migration of lithium ions and affects the rate characteristics of the battery. A balance needs to be made between the two. The usual method in the industry is to adjust the amount of colloid coated on the diaphragm and the temperature and pressure during high-temperature pressurized formation. By optimizing these two conditions, the battery can be balanced to prevent deformation and meet the characteristics of high-rate charge and discharge. Summary of the invention

[0007] The purpose of the present invention is to provide a battery cell, a battery, a preparation method and a device with high rate performance in order to solve the above-mentioned existing problems of batteries, especially polymer batteries using aluminum-plastic films. During the battery cycle, the battery rate characteristics are enhanced without being easily deformed, so that the charge and discharge rate of the battery is significantly improved.

[0008] The present invention provides a battery, preparation method and device with high rate performance. When the battery is formed, the high-temperature softening, cross-linking and swelling characteristics of the polymer are utilized; the conductive agent is used as a tiny particle and is in contact with the electrolyte. After the high-temperature fixture is formed to a certain time and power, the colloid cross-links and swells, and the cross-linking and swelling in this state are sheared and processed by ultrasound under certain conditions, so that the dense cross-linking and sol effects are controlled to a certain extent, and certain gaps are generated to hinder the transmission of lithium ions. The impedance of ion migration is reduced, and the rate characteristics of the battery are actually improved while ensuring the hardness and cycle expansion rate of the battery are low. The cavitation effect of ultrasound has the ability to shear and compress the conductive agent of the tiny conductive particles after contacting the electrolyte, which can effectively play a key role in the uniform distribution of the conductive agent of the tiny particles, which is obvious in the membrane resistivity and high current rate discharge characteristics.

[0009] To achieve the above purpose, the technical solution provided by the present invention is:

[0010] The present invention is achieved through the following technical solutions:

[0011] The first aspect of the present application provides a method for preparing a battery cell with high rate performance, comprising the following steps:

[0012] Applying polymer coating on the battery separator;

[0013] Assembling a separator containing a polymer material coating, a positive electrode sheet containing a positive electrode material, and a negative electrode sheet containing a negative electrode material into a semi-finished battery cell, and then injecting an electrolyte;

[0014] Placing the semi-finished battery cell after the electrolyte is injected between two clamping plates, and applying pressure to the two clamping plates to make the positive electrode sheet, the negative electrode sheet and the separator close together;

[0015] The clamping plates have heating and ultrasonic functions, and the two clamping plates heat the whole body formed by the positive electrode sheet, the negative electrode sheet and the diaphragm in close contact and provide ultrasonic waves; when the semi-finished battery cell is charged and formed for the first time, the polymer material coating on the diaphragm is heated to cause a cross-linking reaction with the positive electrode material on the positive electrode sheet and the negative electrode material on the negative electrode sheet, and the cross-linking reaction product is ultrasonically sheared by applying ultrasonic waves;

[0016] After degassing, sealing and aging, the finished battery cell with high rate performance is obtained.

[0017] To optimize the above technical solutions, the specific measures taken also include:

[0018] The main component of the polymer material coating is a polymer material, and the polymer material is selected from polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trifluoroethylene, polyvinylidene fluoride-chlorotrifluoroethylene, polyacrylonitrile or polymethyl methacrylate.

[0019] Furthermore, the polymer material coating also contains insulating material, and the insulating material is selected from alumina, silica, hydrated alumina or aramid.

[0020] Furthermore, in the polymer material coating, the mass ratio of the polymer material to the insulating material is 1-4:6-9.

[0021] Furthermore, the two clamping plates are used to heat the whole body formed by the positive electrode sheet, the negative electrode sheet and the diaphragm in close contact and provide ultrasonic waves, wherein:

[0022] The clamping plate heats the whole body formed by the positive electrode sheet, the negative electrode sheet and the separator in close contact, and the heating temperature is 70-90°C;

[0023] Providing ultrasonic waves during heating, wherein the ultrasonic waves have an ultrasonic frequency of 25 to 100 KHz, an amplitude of 10 to 100 um, a single ultrasonic time of 0.5 to 15 seconds, an ultrasonic interval of 0.5 to 1.5 minutes, and a cycle number of 10 to 20 times;

[0024] The surface pressure of the two splints is 8~22kg / cm 2 .

[0025] Furthermore, the ultrasonic wave is provided during the heating, specifically, the clamping plate heats the semi-finished battery cell after the electrolyte is injected, and the ultrasonic wave is applied after the semi-finished battery cell is heated to a charge of more than 70%.

[0026] Furthermore, the shearing effect of the cross-linked product between the polymer material coating on the diaphragm and the positive electrode material on the positive electrode sheet and the negative electrode material on the negative electrode sheet is controlled by controlling the parameters of the ultrasonic wave.

[0027] The second aspect of the present application provides a device for preparing high-rate performance battery cells, including a first clamping plate and a second clamping plate, which are used to clamp the semi-finished battery cells after the electrolyte is injected, so that the positive electrode sheet, the negative electrode sheet and the diaphragm of the semi-finished battery cells are tightly attached together; the first clamping plate is provided with a heating device inside, and the temperature is increased by the heating device to heat the semi-finished battery cells; the second clamping plate has an ultrasonic energy transducer and an amplitude transformer built in, and when it is turned on, the ultrasonic wave is transmitted to the semi-finished battery cells through the second clamping plate; the first clamping plate and the second clamping plate are connected to a pressure device, so that the first clamping plate and the second clamping plate are relatively close to each other and clamp the semi-finished battery cells therebetween.

[0028] A third aspect of the present application provides a battery cell, which is prepared by the above method.

[0029] A fourth aspect of the present application provides a battery comprising the above-mentioned battery cell.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] The key of the present invention is to solve the dilemma of improving battery deformation and expansion in the industry.

[0032] In order to improve the deformation and expansion of the battery in the traditional method, a large amount of polymer colloid is coated on the diaphragm. After the colloid swells at high temperature, it cross-links with the polymer in the positive or negative electrode, so that the positive and negative electrodes are firmly bonded together. Although this method can effectively improve the deformation and expansion of the battery, it greatly sacrifices the kinetics of lithium ion migration. Too densely cross-linked tissue will reduce the path of ion migration, making it unable to quickly combine with electrons to react.

[0033] Normally, in order to improve this situation, the industry mainly chooses to apply a small amount of glue on the diaphragm or change the type of glue, but reducing the amount of glue will affect the processing energy of the diaphragm itself during coating. The less glue is applied, the more difficult it is to control the amount, and consistency cannot be guaranteed. Other types of polymers are not very compatible with the electrolyte in the early stages, and it is difficult to quickly swell and cross-link.

[0034] The solution of the present invention solves the above-mentioned problem. It is only necessary to place the diaphragm coated with polymer colloid in the device provided by the present invention after the battery is filled with liquid, and apply pressure by clamping to make the positive electrode, negative electrode and diaphragm close together, and use the clamping plate to heat and ultrasonicate. When the battery is heated and pressurized, the polymer material coated on the diaphragm and the polymer material between the positive electrode and the negative electrode are cross-linked. When the colloid is heated and softened, the vibration effect and cavitation effect of the ultrasonic wave are used to shear the cross-linked glue. By controlling the parameters of the ultrasonic wave, the effect ratio of the polymer cross-linking can be effectively controlled.

[0035] The first clamping plate of the device of the present invention is provided with a heating device inside, and the heating device is used to achieve heating. The second clamping plate is built-in with an ultrasonic energy converter and an amplitude transformer, which can provide ultrasonic transmission to the battery at any time and at a fixed time. When the ultrasonic wave propagates in the electrolyte liquid, it generates high-frequency vibrations, which act on the conductive agent particle clusters in contact with the liquid, breaking them up through shear force and compression force. At the same time, the high-pressure shock wave generated by the instantaneous collapse of the bubbles formed by the cavitation effect further promotes the dispersion of the conductive agent particles, and the thermal effect will also change the surface properties of the particles. The two work together to enhance the dispersion effect. The uniform dispersion of the conductive agent helps to evenly distribute the electrons, evenly distribute the current density, and improve the electrochemical performance of the battery, especially the significant improvement of high-rate charging and discharging.

[0036] The solution of the present invention fills the technical gap in the industry for this problem, especially considering the high temperature and pressure characteristics of high-rate lithium-ion batteries during formation, the characteristics of the diaphragm coating material that makes the battery hard, and the characteristics of the conductive agent and electrolyte liquid necessary in the electrode sheet. The present invention optimizes and renovates the formation device, inserts an ultrasonic structural part, and performs ultrasonic action continuously or uninterruptedly when the formation reaches a certain amount of electricity:

[0037] The diaphragm, positive electrode and negative electrode with PVDF coating are sheared under high temperature by ultrasonic action, which produces a cross-linking effect, and the cross-linking is loose. The area of ​​the gaps is conducive to the rapid migration of lithium ions, thereby enhancing the rate characteristics of the battery.

[0038] The separator, positive electrode and negative electrode with polyacrylic acid coating are in a state of shearing after ultrasonic action at high temperature, and the colloid swells and bonds, the swelling area is reduced, the link state between the colloid particles is reduced, and the area of ​​the gap is conducive to the rapid migration of lithium ions, thereby enhancing the rate characteristics of the battery.

[0039] When preparing the diaphragm coating material, the present invention also mixes the polymer material with the insulating material. The polymer material can be cross-linked with the polymer material of the electrode to form a polymer colloid to achieve a bonding effect, and the insulating material is evenly distributed on the surface of the diaphragm and forms a skeleton effect with the cross-linked colloid of the polymer material, which significantly improves the thermal shrinkage performance of the diaphragm.

[0040] During high temperature formation, the conductive agent is uniformly attached to the material particles and evenly dispersed between the particle chains after ultrasonic vibration, shearing and compression effects, which greatly reduces the situation where the local conductive agent is too strong or too weak. The uniform dispersion of the conductive agent can effectively reduce the film resistivity of the pole piece and improve the rate characteristics of the battery.

[0041] The present invention is simple in process flow, does not need to add additional process steps to process the battery, can be directly integrated on the formation device, has simple cost and process, is easy to promote, and has insignificant cost investment while significantly improving performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 : Schematic diagram of the placement of batteries and formation equipment.

[0043] Figure 2 : Schematic diagram of battery location and ultrasonic effect.

[0044] Figure 3 : Schematic diagram of the microscopic effects before and after cross-linking swelling and ultrasonic action.

[0045] Figure 4 : Schematic diagram of conductive agent particles and microscopic effects before and after ultrasonic action. DETAILED DESCRIPTION

[0046] The above contents of the present invention are further described in detail below in the form of embodiments, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments, and all technologies realized based on the above contents of the present invention belong to the scope of the present invention.

[0047] The experimental methods used in the following examples are all conventional methods unless otherwise specified, and the reagents, methods and equipment used are all conventional reagents, methods and equipment in the technical field unless otherwise specified.

[0048] The present invention provides a method for preparing a battery cell with high rate performance, comprising the following steps:

[0049] Applying polymer coating on the battery separator;

[0050] Assembling a separator containing a polymer material coating, a positive electrode sheet containing a positive electrode material, and a negative electrode sheet containing a negative electrode material into a semi-finished battery cell, and then injecting an electrolyte;

[0051] Place the semi-finished battery cell after the electrolyte is injected between two clamping plates, and apply pressure to the two clamping plates to make the positive electrode sheet, the negative electrode sheet and the separator stick together;

[0052] The clamping plates have heating and ultrasonic functions, and the two clamping plates heat the whole body formed by the positive electrode sheet, the negative electrode sheet and the diaphragm in close contact and provide ultrasonic waves; when the semi-finished battery cell is charged and formed for the first time, the polymer material coating on the diaphragm is heated to cause a cross-linking reaction with the positive electrode material on the positive electrode sheet and the negative electrode material on the negative electrode sheet, and the cross-linking reaction product is ultrasonically sheared by applying ultrasonic waves;

[0053] After degassing, sealing and aging, the finished battery cell with high rate performance is obtained.

[0054] The main component of the polymer material coating is the polymer material, or a mixture of the polymer material and the insulating material. In the polymer material coating, the mass ratio of the polymer material to the insulating material is 1-4:6-9.

[0055] The two clamping plates heat the whole body formed by the positive electrode sheet, the negative electrode sheet and the diaphragm and provide ultrasonic waves, wherein:

[0056] The clamping plate heats the whole body formed by the positive electrode sheet, the negative electrode sheet and the separator, and the heating temperature is 70-90°C;

[0057] Ultrasonic waves are provided during heating. The ultrasonic waves provided in the present invention are between 20 and 100 KHz, the single continuous time of the ultrasonic waves is 0.1 to 20 seconds, the interval can be cycled, and the amplitude range is 10 to 200 um.

[0058] Preferably, the ultrasonic wave has an ultrasonic frequency of 25 to 100 KHz, an amplitude of 10 to 100 um, a single ultrasonic time of 0.5 to 15 s, an ultrasonic interval of 0.5 to 1.5 min, and a cycle number of 10 to 20 times.

[0059] The surface pressure of the two splints is 8~22kg / cm 2 .

[0060] Ultrasonic waves are provided during heating, specifically, the clamping plate heats the semi-finished battery cell after the electrolyte is injected, and ultrasonic waves are applied after the semi-finished battery cell is heated to a charge of more than 70%.

[0061] The shearing effect of the cross-linked product between the polymer material coating on the diaphragm and the positive electrode material on the positive electrode sheet and the negative electrode material on the negative electrode sheet is controlled by controlling the parameters of the ultrasonic wave.

[0062] The present application also provides a device for preparing high-rate performance battery cells, including a first clamping plate and a second clamping plate, which are used to clamp the semi-finished battery cells after the electrolyte is injected, so that the positive electrode sheet, the negative electrode sheet and the diaphragm of the semi-finished battery cells are tightly attached together; a heating device is provided inside the first clamping plate, and the temperature is increased by the heating device to heat the semi-finished battery cells; the second clamping plate has an ultrasonic energy transducer and an amplitude transformer built in, and when it is turned on, ultrasonic waves are transmitted to the semi-finished battery cells through the second clamping plate; the first clamping plate and the second clamping plate are connected to a pressure device, so that the first clamping plate and the second clamping plate are relatively close to each other and clamp the semi-finished battery cells therebetween.

[0063] The present application also provides a battery cell, which is prepared by the above method.

[0064] The present application also provides a battery comprising the above-mentioned battery cell.

[0065] The technical solution of the present invention is further described in detail below in conjunction with specific implementation methods:

[0066] The present invention first coats the polymer material on the diaphragm, and then winds or stacks the diaphragm with the positive electrode and the negative electrode to make an electrode group; the diaphragm is encapsulated in an aluminum-plastic film or a metal shell, and an electrolyte is injected to obtain a semi-finished battery cell. When the semi-finished battery cell is first formed, the device provided in the present application is used for formation, such as Figure 1 As shown:

[0067] 1 is the conduction shaft of the device, which mainly provides pressure through a motor, a cylinder or a gas-liquid booster cylinder;

[0068] 2 is the pressure plate A, which is mainly used to press the battery. At the same time, there is an electric heating tube inside, which can achieve temperature increase;

[0069] 3 is a pressure plate B, which, in addition to pressing the battery, has a built-in ultrasonic energy converter and amplitude transformer. When the ultrasonic wave is turned on, it is transmitted through this plate to act on the battery.

[0070] 4 is a semi-finished battery cell, 5 is a positive electrode, and 6 is a negative electrode; the battery polarity is introduced into a wire or a contact-type metal by a known method to realize the voltage monitoring and current transmission of the battery, so that the battery is used for formation and charging and discharging;

[0071] 7 is the power supply and temperature controller of the heating plate;

[0072] 8 is an ultrasonic controller;

[0073] 9 is the power supply of the ultrasonic wave.

[0074] This device is to clamp the semi-finished battery cell after liquid injection between two plates. In addition to bearing the pressure of the conduction shaft, the pressing plate A can realize the heating function, so that the temperature can be adjusted during battery formation. The pressing plate B mainly integrates the ultrasonic energy converter and amplitude transformer; when the battery is heated and pressurized, the polymer material coated on the diaphragm is cross-linked with the polymer material between the positive and negative electrodes. Under high temperature, the tape softens, and the vibration effect and cavitation effect of the ultrasonic wave can be used to shear the cross-linked glue.

[0075] Figure 2 For another implementation:

[0076] Wherein 10 is a pressure plate C, which mainly provides heating and applies pressure;

[0077] 12 is a pressure plate D, which mainly increases the applied pressure and the generation of ultrasonic waves;

[0078] 11 is a semi-finished battery cell sandwiched between two plates;

[0079] 13 is a schematic diagram of the emission and reflection of ultrasonic waves;

[0080] 14 is an expanded schematic diagram, and 15 is a closed schematic diagram.

[0081] During high-temperature formation, ultrasonic waves can be provided at any time. When ultrasonic waves are transmitted to the battery, they will modify the cross-linked polymer materials inside the battery at high temperatures, which can effectively control the bonding and cross-linking effect. After the ultrasonic waves pass through the battery body, they will shear the cross-linked state, and gaps will appear in the sheared cross-linked areas. The gaps here help the flow of electrolyte to increase the wetting effect and increase the channels for lithium ion migration over a large area. Therefore, this method can not only not cause great damage to the adhesion of the diaphragm, positive electrode, and negative electrode, but also increase many channels to meet the migration of lithium ions, thereby improving the rate characteristics of the battery.

[0082] Microscopic effect diagram Figure 3 :

[0083] 16 is a PVDF-type separator coating, which is cross-linked with the positive electrode and the negative electrode at high temperature: the cross-linking is dense;

[0084] 17 is a PVDF diaphragm coating. The positive and negative electrodes are sheared under high temperature and ultrasonic action, which has a cross-linking effect: the cross-linking is loose, and the area of ​​the gap is conducive to the rapid migration of lithium ions. Enhance the rate characteristics of the battery;

[0085] 18 is a polyacrylic acid separator coating. The positive and negative electrodes are colloidally swollen and bonded under high temperature conditions: the swollen area is large and dense;

[0086] 19 is a polyacrylic acid separator coating. The positive and negative electrodes are in a state of shearing under ultrasonic action at high temperature. The effect of colloid swelling and bonding is as follows: the swelling area is reduced, the linking state between the colloid particles is reduced, and the area of ​​the gap is conducive to the rapid migration of lithium ions, thereby enhancing the rate characteristics of the battery.

[0087] During high-temperature formation, the device of the present invention can provide ultrasonic transmission to the battery at any time. When the ultrasonic wave propagates in the electrolyte, it generates high-frequency vibration, which acts on the conductive agent particle clusters in contact with the liquid, breaking them up through shear force and compression force. At the same time, the high-pressure shock wave generated by the instantaneous collapse of the bubbles formed by the cavitation effect further promotes the dispersion of the conductive agent particles. The thermal effect will also change the surface properties of the particles and enhance the dispersion effect. The uniform dispersion of the conductive agent helps to evenly distribute the electrons, evenly distribute the current density, and improve the electrochemical performance of the battery, especially for high-rate charging and discharging. Figure 4 :

[0088] 20 is the state of the conductive agent particles in the positive electrode and the negative electrode. The large gaps between the electrode material particles will easily lead to the accumulation of the conductive agent, resulting in the same proportion of conductive agent usage, local conductivity is too strong and local conductivity is too weak; the diaphragm resistivity of the electrode is relatively high, which has a significant impact on the distribution of current density.

[0089] 21 is the state of high-temperature formation, after ultrasonic vibration, shear and compression effects, the conductive agent is evenly attached to the material particles and evenly dispersed between the particle chains; the situation where the local conductive agent is too strong or too weak is greatly reduced; the uniform dispersion of the conductive agent can effectively reduce the diaphragm resistivity of the electrode and improve the rate characteristics of the battery.

[0090] In some embodiments of the present application, the positive electrode is mainly made of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, ternary materials, binary materials, etc., equipped with polymer colloids (PVDF, etc.) and solvents (NMP, etc.), and the slurry is coated on aluminum foil after being prepared. After rolling, it is cut into corresponding sizes according to the size design of different batteries to obtain a positive electrode sheet. The negative electrode mainly includes carbon-based materials, natural graphite, artificial graphite, soft carbon, hard carbon, carbon fiber, etc., and non-carbon-based materials mainly include silicon substrates, tin-based materials, lithium-containing transition metal nitrides, alloy negative electrode materials, nano-scale negative electrode materials, etc. Including carbon-based and non-carbon-based negative electrodes mixed in proportion. Equipped with polymer colloids (CMC, etc.), a binder (SBR, etc.) is added and slurry is obtained after homogenization. The slurry is coated on the surface of copper foil, baked, rolled, and cut into corresponding sizes according to the size design of different batteries to obtain a negative electrode sheet.

[0091] In some embodiments of the present application, the composition of the polymer slurry of the diaphragm substrate and the surface coating is as follows:

[0092] The diaphragm substrate is mainly composed of polyethylene PE, polypropylene PP, and PE / PP composite film.

[0093] The coating material is mainly composed of a single polymer material or a polymer material mixed with other insulating materials. The polymer material in the present invention includes, but is not limited to, the following: polyvinylidene fluoride PVDF, vinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyvinylidene fluoride-trifluoroethylene (PVDF-TrFE), polyvinylidene fluoride-chlorotrifluoroethylene (PVDF-CTFE), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), and the coating weight of the tape is 0.05-0.3 g / m2.

[0094] The polymer material is mixed with the insulating material. The polymer material can be cross-linked with the polymer material of the electrode to form a polymer colloid to achieve a bonding effect, while the insulating material is evenly distributed on the surface of the diaphragm and forms a skeleton effect with the cross-linked colloid of the polymer material, which significantly improves the thermal shrinkage performance of the diaphragm.

[0095] In some embodiments of the present application, the insulating material mainly includes alumina (Al2O3), silicon dioxide (SiO2), hydrated alumina (γ-AlOOH), aramid and other high heat-resistant polymers.

[0096] In some embodiments of the present application, the electrolyte of the battery is mainly composed of a solvent and an electrolyte lithium salt, and the solvent mainly includes ethylene carbonate (EC), diethyl carbonate (DEC), etc. In addition, functional additives are also added to the electrolyte, such as film-forming stabilizing additives, vinyl sulfate (VEC) lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), etc.

[0097] In some embodiments of the present application, the battery mainly adopts a polymer aluminum-plastic composite film or a thin metal shell, and the main function of the shell is to protect the electrode group and isolate impurities and moisture.

[0098] In some embodiments of the present application, the battery process mainly includes: the main material and auxiliary material of the positive electrode are mixed together through slurry, and the positive electrode sheet is obtained through coating, drying, rolling and shearing. The main material and auxiliary material of the negative electrode are mixed together through slurry, and the negative electrode sheet is obtained through coating, drying, rolling and shearing. The obtained positive and negative electrode sheets are combined with the coated isolation membrane. The electrode group is obtained through winding or lamination process. After the electrode group is shelled, baked and injected with electrolyte, a semi-finished battery cell is obtained. The semi-finished battery cell enters the clamping, heating and ultrasonic integrated device provided by the present invention for the first charging. After degassing, sealing, aging and sorting processes, the finished battery cell is obtained.

[0099] For the sake of simplicity, this document only specifically discloses some numerical values ​​and optional ranges. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range. Similarly, any upper limit can be combined with any other upper limit to form an unambiguous range; the optional items in the optional range can also be combined arbitrarily.

[0100] Unless otherwise specified, the terms used in this application have the well-known meanings commonly understood by those skilled in the art. Unless otherwise specified, the values ​​of the parameters mentioned in this application can be measured by various measurement methods commonly used in the art. For example, the film resistivity test method in the present invention is: take a certain area of ​​the electrode, use aluminum foil or copper foil of the same thickness, measure the thickness, use the same current time to act on the electrode, calculate the resistance and calculate the resistivity.

[0101] The method of shearing and dispersing cross-linking and agglomeration in the present invention is to utilize the polymer colloid to swell in the electrolyte, change with the increase of temperature, become soft, and solidify by charging, heating and ultrasonic three processes. Among them, charging mainly makes the electrode fully expand, opening more channels, which is more conducive to the wetting of the electrolyte; heating mainly accelerates the swelling of the polymer colloid of the diaphragm coating by the electrolyte solvent, so that it can be cross-linked with the polymer colloid between the positive and negative electrodes; while heating at high temperature, the cross-linking and swelling states increase; at this time, ultrasonic treatment is regularly performed on it, and the state after ultrasonic shearing: the diaphragm, positive electrode and negative electrode with PVDF coating are in a state of high temperature and sheared by ultrasonic action, and a cross-linking effect is produced, and the cross-linking is loose, and the area of ​​the gaps therein is conducive to the rapid migration of lithium ions, thereby enhancing the rate characteristics of the battery; the diaphragm, positive electrode and negative electrode with polyacrylic acid coating are in a state of high temperature and sheared by ultrasonic action, and the colloid is swollen and bonded, the swelling area is reduced, the linking state between the colloid particles is reduced, and the area of ​​the gaps is conducive to the rapid migration of lithium ions, thereby enhancing the rate characteristics of the battery.

[0102] During high-temperature formation, after ultrasonic vibration, shearing and compression effects, the conductive agent is evenly attached to the material particles and evenly dispersed between the particle chains. This greatly reduces the situation where the local conductive agent is too strong or too weak. The uniform dispersion of the conductive agent can effectively reduce the film resistivity of the pole piece and improve the rate characteristics of the battery.

[0103] The above-mentioned splint heating methods of the present invention include, but are not limited to, the following methods: resistance heating, induction heating, arc heating, infrared heating, and the heating temperature is between 70 and 90°C.

[0104] The ultrasonic wave set in the present invention is between 20 and 100 KHz, the single continuous time of the ultrasonic wave is 0.1 to 20 seconds, the interval can be cyclic, and the amplitude range is 10 to 200 um.

[0105] In some embodiments of the present invention, the positive electrode colloid of the battery mainly includes PVDF colloid, accounting for 0.3-2%. The negative electrode colloid mainly includes CMC and SBR colloid, accounting for 1%-3% by weight.

[0106] In some embodiments of the present invention, the battery used is a lithium-ion battery, and in other embodiments of the present invention, the battery used is a sodium-ion battery. The solutions of the present invention are not limited to the use of the above types of batteries.

[0107] The positive electrode, negative electrode and electrolyte in the following examples and comparative examples are all made of known lithium-ion battery materials.

[0108] Comparative Example 1:

[0109] The dimensions of lithium-ion batteries are as follows: thickness 9.9mm, width 40mm, length 58mm, battery capacity 5Ah, PVDF coating on the surface of the diaphragm, PVDF coating is mainly made of PVDF dissolved in NMP and other solvents to make glue, and the diaphragm is coated with PVDF glue on the surface of the diaphragm by dip coating or roller coating. After coating, it is rolled to the oven for baking, and the solvent is baked and volatilized to obtain the finished diaphragm. The internal pole group structure is mainly wound, and the battery is assembled and injected with electrolyte. The semi-finished battery is aged by high-temperature static. The aged battery is formed by the clamp pressure to activate the lithium-ion battery and charge it. After degassing, edge sealing, edge cutting, aging, capacity, voltage, and internal resistance testing, the finished lithium-ion battery is obtained. The finished battery is disassembled and separated, and the peel strength between the diaphragm and the positive and negative electrodes is measured. The resistivity data of the positive and negative electrodes are measured. The internal resistance of the finished battery is measured, and the platform voltage is confirmed by charging with a large current, and the discharge platform voltage and retention rate data are confirmed by discharging with a large current. The battery is charged and discharged with a large current for 500 cycles, and the battery thickness expansion growth rate is measured during the period.

[0110] Embodiments 1 to 7:

[0111] The dimensions of lithium-ion batteries are as follows: thickness 9.9mm, width 40mm, length 58mm. The battery capacity is 5Ah. The positive electrode, negative electrode, and electrolyte inside the battery are all made of known lithium-ion battery materials. The surface of the diaphragm is coated with PVDF. The PVDF coating is mainly made of PVDF dissolved in solvents such as NMP to make a glue. The diaphragm is coated with PVDF glue on the surface of the diaphragm by dip coating or roller coating. After coating, it is rolled to the oven for baking. After the solvent is baked and volatilized, a diaphragm with a coating is obtained. The internal pole group structure is mainly wound. After the battery is assembled and injected with electrolyte, it is placed at high temperature for electrolyte infiltration.

[0112] The device of the present invention is used to clamp and press the semi-finished battery cell (surface pressure 12kg / cm 2 ), the total amount of electricity is 90%, heated and charged, wherein the battery charging heating temperature is 80°C, and the state of electricity at different stages is used as the starting point: 60%, 70%, 75%, 80%, 85%, 90%, 100%, corresponding to Examples 1 to 7 respectively. The battery is treated with synchronous ultrasound, with a single ultrasound time of 0.5S, an ultrasound frequency of 25KHz, an amplitude of 10um, an ultrasound interval of 1min, and a cycle number of 10 times. After the treated battery, the lithium-ion battery is activated and charged, and then degassing, edge sealing, edge cutting, aging, and detection of capacity, voltage, and internal resistance are performed to obtain a finished lithium-ion battery. The finished battery is disassembled and separated, and the peel strength between the diaphragm and the positive electrode and the negative electrode is measured. The resistivity data of the positive and negative electrodes are measured. The finished battery measures the internal resistance, and the platform voltage is confirmed by charging with a large current, and the discharge platform voltage and retention rate data are confirmed by discharging with a large current. The battery is subjected to a large current charge and discharge cycle of 500 weeks, and the battery thickness expansion growth rate during the measurement period is measured.

[0113] Embodiments 8 to 12:

[0114] Examples 8 to 12 use the same state of charge starting point (80%) as Example 4 to perform step verification on the battery charging temperature, and other parameters are the same as Example 4.

[0115] The battery charging heating temperatures of Examples 8 to 12 are 60°C, 70°C, 85°C, 90°C, and 100°C, respectively.

[0116] Embodiments 13 to 16:

[0117] Examples 8 to 12 use the same starting point of the state of charge as Example 4 (80%) to perform step verification on the ultrasonic frequency, and other parameters are the same as Example 4.

[0118] The ultrasonic frequencies of Examples 13 to 16 are 20 KHz, 50 KHz, 100 KHz, and 110 KHz, respectively.

[0119] Embodiments 17 to 21:

[0120] Examples 8 to 12 use the same starting point of the state of charge as Example 4 (80%) to perform step verification on the ultrasonic amplitude, and other parameters are the same as Example 4.

[0121] The ultrasonic amplitudes of Examples 17 to 21 are 5um, 30um, 60um, 100um, and 110um, respectively.

[0122] Embodiments 22 to 26:

[0123] Examples 22 to 26 use the same starting point of the power state as Example 4 (80%), and perform step verification on the single ultrasonic time. Other parameters are the same as Example 4.

[0124] The single ultrasonic time of Examples 22 to 26 is 0.1S, 3S, 10S, 15S, and 20S, respectively.

[0125] Embodiments 27 to 29:

[0126] Examples 27 to 29 use the same starting point of the state of charge as Example 4 (80%) to perform step-by-step verification on the number of ultrasonic cycles, and other parameters are the same as Example 4.

[0127] The number of ultrasonic cycles in Examples 27 to 29 are 15, 20, and 25, respectively.

[0128] Embodiment 30~31:

[0129] Examples 30 to 31 use the same charge state starting point (80%) as Example 4 to compare and verify the materials coated on the diaphragm, and other parameters are the same as Example 4.

[0130] The materials used for coating the diaphragms of Examples 30 to 31 are PVDF-HFP coating and PMMA coating respectively:

[0131] PVDF-HFP coating: PVDF-HFP is dissolved in NMP and other solvents to make glue. The PVDF-HFP glue is coated on the surface of the diaphragm by dip coating or roller coating. After coating, it is rolled into an oven for baking. After the solvent is baked and volatilized, the finished diaphragm is obtained.

[0132] PMMA coating: PMMA is mixed in water to prepare slurry, and the water-soluble PMMA is evenly rolled or sprayed on the diaphragm. The diaphragm is baked in a roller oven, and the water solvent evaporates to obtain a finished diaphragm.

[0133] Embodiments 32 to 36

[0134] Examples 32 to 36 use the same charge state starting point (80%) as Example 4 to compare and verify the material ratio of the diaphragm coating, and other parameters are the same as Example 4.

[0135] The material coated on the diaphragm of Examples 32 to 36 is a PVDF-γ-AlOOH coating: PVDF and γ-AlOOH are dissolved in a solvent such as NMP to prepare a glue solution, and the glue is coated on the surface of the diaphragm by dipping, rolling or spraying. After coating, it is rolled to an oven for baking, and the solvent is baked and volatilized to obtain a finished diaphragm. The ratios of PVDF to γ-AlOOH in Examples 32 to 36 are 1:9, 2:8, 3:7, 4:6, and 5:5, respectively.

[0136] According to the above-described method, the coating material, formation temperature, formation pressure, formation quantity, ultrasonic starting quantity, ultrasonic time, ultrasonic frequency, ultrasonic amplitude, ultrasonic interval, and ultrasonic times formed are shown in Table 1.

[0137] The test results of the finished battery obtained according to the above-described method include the bonding strength between the diaphragm and the positive electrode, the bonding strength between the diaphragm and the negative electrode, the resistivity of the positive electrode diaphragm, the resistivity of the negative electrode diaphragm, the internal resistance of the battery, the platform voltage of 2C charging, the platform voltage of 5C discharging, the retention rate of 5C discharge capacity, and the thickness expansion growth rate of the battery after 500 cycles, as shown in Table 2.

[0138]

[0139] Table 1

[0140]

[0141] Table 2

[0142] The scheme of the present invention is adopted, and the experimental verification results are as follows:

[0143] Examples 1 to 7 mainly use the same ultrasonic parameters to verify the gradient of the initial charge of formation. Compared with the comparative example, the bonding strength between the diaphragm and the positive electrode, and the bonding strength between the negative electrode and the diaphragm in the ultrasonically treated examples are significantly reduced. The diaphragm resistance of the positive and negative electrodes is reduced, and the charging and discharging platforms are improved. The large current discharge retention rate is increased, and there is no significant increase in cyclic expansion. The initial charge below 60% has no significant improvement in the bonding strength of the positive and negative electrodes. The effect is produced after the semi-finished battery cell is heated to more than 70% of the charge. The effect increases gradually from 90% to 100% of the charge. It is preferred to start applying ultrasound after the semi-finished battery cell is heated to more than 70% of the charge.

[0144] In Examples 8 to 12, the same formation parameters and ultrasonic parameters as in Example 4 were verified, and the formation temperature was gradient-compared. The increase in formation temperature is conducive to the softening of the polymer colloid. The increase in formation temperature will significantly reduce the bonding strength of the positive and negative electrodes, significantly reduce the film resistance of the positive and negative electrodes, increase the charge and discharge platform, and the large current discharge rate and the expansion rate after the cycle do not change significantly. When the temperature is 60 degrees, because it has not yet reached the temperature for deep dissolution of the colloid, the bonding strength is not significantly improved. After the temperature increases to 100 degrees, overheating will cause the bonding strength of the glue to decrease significantly. The preferred battery charging heating temperature range is 70 to 90 degrees.

[0145] Examples 13 to 16 were verified with the same formation parameters and different ultrasonic parameter frequencies as in Example 4. With the increase in frequency, the bonding strength and the sheet resistance of the positive and negative electrodes will change slightly, but the performance of large current discharge will be significantly improved. The effect of ultrasonic frequency is not obvious at 20KHz, and the effect is weakened above 100KHz. The preferred ultrasonic frequency is 25 to 100KHz.

[0146] In Examples 17 to 21, the same formation parameters as in Example 4 were used, and different ultrasonic parameter frequencies were used for verification, and the amplitude gradient was verified. As the amplitude increased, the diaphragm resistance and the battery internal resistance increased. When the amplitude was too low to 5um, the bonding strength did not change significantly. When the amplitude increased to 100um, the rate characteristic effect did not increase significantly. The amplitude was preferably between 10 and 100um.

[0147] Examples 22 to 26 were verified with different ultrasonic parameter times compared with Example 4. As the single ultrasonic time increased, the bonding strength of the positive and negative electrodes decreased, the resistance of the positive and negative electrode membranes decreased, the charge and discharge platform increased, and the large current discharge rate increased. The expansion was reduced, and the main reason for the reduction was that the ultrasonic time was prolonged, the shearing of the cross-linked state was more sufficient, and the dispersion of the conductive agent was more uniform. This reduced the impedance of ion migration and the impedance of electron movement. The single ultrasonic time was too short, 0.1S, and the effect was not obvious. However, after the single ultrasonic time was increased to 15s, the effect weakened gently, and the preferred single ultrasonic time was 0.5 to 15S.

[0148] Examples 27 to 29 were verified with the same formation parameters and ultrasonic parameters as Example 4, but with different ultrasonic cycle times. The increase in the number of times slightly increased the effect of ultrasound, and after 20 times of ultrasound, the effect increase was not obvious. The preferred condition was 10 to 20 times.

[0149] Examples 30-31 were investigated with the same formation parameters, the same ultrasonic parameters, and the differences in membrane coating materials as in Example 4. The membranes were coated with PVDF-HFP copolymer coating and PMMA colloid coating, respectively, and both could be sheared by initial ultrasound in the cross-linked and hot-melt states, which increased the channels for electrolyte flow and enhanced ion migration, thereby improving the rate characteristics of the battery.

[0150] Examples 32 to 36 were conducted with the same formation parameters and ultrasonic parameters as Example 4. The only difference was the membrane coating material, and the ratio between the membrane colloid and the insulating material was different. Different ratios will affect the bonding strength. Too low a ratio of glue will result in weak bonding strength, and too high a ratio of glue will have no obvious effect on the battery pole piece and battery test data due to its interaction with the insulator. The preferred solution is a mass ratio of polymer material to insulating material of 1 to 4:6 to 9.

[0151] In summary, it is verified that the high-rate characteristics of a single diaphragm coating, without treatment by the method of the present invention, are obviously not as good as those of the solution after ultrasonic treatment. The present invention is simple and practical, and can simultaneously meet the requirements of battery bonding and battery initial formation activation charging. At the same time, by using the device of the present invention, while heating, the colloids in the electrode material and the diaphragm material soften, and ultrasound shears the colloids in the softened state, which can effectively control the bonding area, so as not to deform the battery while improving the rate discharge performance of the battery. Under high temperature conditions, the reduction in the viscosity of the electrolyte can cavitate and squeeze the fine conductive agents in the positive and negative electrode materials, which can effectively make the conductive agents more evenly dispersed, comprehensively improve the ability of electron migration, and significantly improve the rate discharge characteristics of the battery.

[0152] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, according to the technical essence of the present invention, any simple modification, equivalent replacement and improvement made to the above embodiment still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a battery cell with high rate performance, characterized in that: The following steps are involved: Applying polymer coating on the battery separator; Assembling a separator containing a polymer material coating, a positive electrode sheet containing a positive electrode material, and a negative electrode sheet containing a negative electrode material into a semi-finished battery cell, and then injecting an electrolyte; Placing the semi-finished battery cell after the electrolyte is injected between two clamping plates, and applying pressure to the two clamping plates to make the positive electrode sheet, the negative electrode sheet and the separator close together; The clamping plates have heating and ultrasonic functions, and the two clamping plates heat the whole body formed by the positive electrode sheet, the negative electrode sheet and the diaphragm in close contact and provide ultrasonic waves; when the semi-finished battery cell is charged and formed for the first time, the polymer material coating on the diaphragm is heated to cause a cross-linking reaction with the positive electrode material on the positive electrode sheet and the negative electrode material on the negative electrode sheet, and the cross-linking reaction product is ultrasonically sheared by applying ultrasonic waves; After degassing, sealing and aging, the finished battery cell with high rate performance is obtained.

2. The method for preparing a battery cell with high rate performance according to claim 1, characterized in that: The main component of the polymer material coating is a polymer material, and the polymer material is selected from polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trifluoroethylene, polyvinylidene fluoride-chlorotrifluoroethylene, polyacrylonitrile or polymethyl methacrylate.

3. The method for preparing a battery cell with high rate performance according to claim 2, characterized in that: The polymer material coating also contains insulating material, and the insulating material is selected from alumina, silicon dioxide, hydrated alumina or aramid.

4. The method for preparing a battery cell with high rate performance according to claim 3, characterized in that: In the polymer material coating, the mass ratio of the polymer material to the insulating material is 1-4:6-9.

5. The method for preparing a battery cell with high rate performance according to claim 1, characterized in that: The two clamping plates are used to heat the whole body formed by the positive electrode sheet, the negative electrode sheet and the diaphragm and provide ultrasonic waves, wherein: The clamping plate heats the whole body formed by the positive electrode sheet, the negative electrode sheet and the separator in close contact, and the heating temperature is 70-90°C; Providing ultrasonic waves during heating, wherein the ultrasonic waves have an ultrasonic frequency of 25 to 100 KHz, an amplitude of 10 to 100 um, a single ultrasonic time of 0.5 to 15 seconds, an ultrasonic interval of 0.5 to 1.5 minutes, and a cycle number of 10 to 20 times; The surface pressure of the two splints is 8~22kg / cm 2 .

6. The method for preparing a battery cell with high rate performance according to claim 5, characterized in that: The ultrasonic wave is provided during the heating, specifically, the clamping plate heats the semi-finished battery cell after the electrolyte is injected, and the ultrasonic wave is applied after the semi-finished battery cell is heated to a charge of more than 70%.

7. The method for preparing a battery cell with high rate performance according to claim 1, characterized in that: The shearing effect of the cross-linked product between the polymer material coating on the diaphragm and the positive electrode material on the positive electrode sheet and the negative electrode material on the negative electrode sheet is controlled by controlling the parameters of the ultrasonic wave.

8. A device for preparing a high-rate performance battery cell, characterized in that: It comprises a first clamping plate and a second clamping plate, which are used to clamp the semi-finished battery cell after the electrolyte is injected, so that the positive electrode sheet, the negative electrode sheet and the diaphragm of the semi-finished battery cell are tightly attached together; the first clamping plate is provided with a heating device inside, and the temperature is increased by the heating device to heat the semi-finished battery cell; the second clamping plate is built-in with an ultrasonic energy converter and an amplitude transformer, and when it is turned on, the ultrasonic wave is transmitted to the semi-finished battery cell through the second clamping plate; the first clamping plate and the second clamping plate are connected to a pressure device, so that the first clamping plate and the second clamping plate are relatively close to clamp the semi-finished battery cell therein.

9. A battery cell, characterized in that: The battery cell is prepared by the method described in any one of claims 1 to 7.

10. A battery, characterized in that: A battery cell comprising the battery cell according to claim 9.

Citation Information

Patent Citations

  • Forming and capacity grading method for nude cells of lithium battery based on high-temperature pressure clamp

    CN106450471A

  • Formation method and formation system of lithium ion battery, lithium ion battery and electric vehicle

    CN109818093A

  • Formation method of lithium ion battery

    CN116154314A

  • Quick-charge and quick-discharge type lithium battery and preparation method thereof

    CN119153803A

  • Cathode material for lithium ion secondary batteries, cathode member for lithium ion secondary batteries, and lithium ion secondary battery

    US20140227597A1